Evaluation of hydrophilic cellulose nanofiber dispersions in a hydrophobic isotactic polypropylene composite. Issue 8 (7th September 2020) - Morita, Akitoshi; Matsuba, Go; Fujimoto, Megumi
Abstract: An effective approach for the evaluation of dispersed hydrophilic cellulose nanofibers (CNFs) in hydrophobic isotactic polypropylene (iPP) is presented using scattering and microscopic techniques for fiber analysis on nanometer and micrometer scales. iPP composites reinforced with CNF fibrous fillers were characterized by small‐angle light scattering, small‐angle X‐ray scattering, and polarized optical microscopy measurements in the molten state in order to evaluate the shape of CNF fillers and/or larger aggregates formed from these fibers. The best dispersion results in the molten state coincided with low concentrations of CNFs. We observed the effect of CNFs on the acceleration of iPP crystal growth using wide‐angle X‐ray scattering and differential scanning calorimeter measurements. It was even possible to observe the nucleation morphology around CNF fibrous fillers using transmission electron microscopy. Abstract :